Krypton. The complete second & final season [videorecording (DVD)] - Cuffe, Cameron, 1993-; Campbell, Georgina, 1992-; Sipos, Shaun, 1981-; Cowan, Elliot, 1976-; Ogbomo, Ann; Pierre, Aaron; Hardiker, Rasmus, 1985-; Day, Wallis, 1994-; Ritson, Blake; McElhinney, Ian, 1948- (Warner Bros. Home Entertainment, 2020)
Season two brings viewers back to a changed Kandor, locked in a battle over its freedom and its future. With Zod now in control, he's on a ruthless mission to rebuild Krypton according to his ideals and to secure its future by conquering the universe. Faced with a bleak outlook, Seg-EI attempts to unite a dispersed group of resisters in an effort to defeat Zod and restore hope to their beloved planet.